THE UTILIZATION OF BLOTONG, MOLASSES, BRAN, AND COCONUT HUSK INTO COMPOST USING MOL OF STALE RICE AND Trichoderma sp. - Hilda Fitria Nurul Huda; Putri Fakhirah Ramadhani; Endang Kusumawati; Mukhtar Ghozali (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Compost is a solution for dealing with organic waste. Compost with organic material must be mixed according to its elemental composition. Protein and potassium are obtained from bran and coconut husk. Blotong contains phosphorus (P), while molasses contains total N and K2O. Local Microorganisms (MOL) of stale rice is an activator to increase the microbiological decomposition of organic matter and contains Saccharomyces cerevisiae, Bacillus cereus, and Aspergillus sp. The addition of Trichoderma sp. can speed up the composting process. The aim of the study is to determine the effect of adding Blotong and bran on the quality of compost, to obtain the most effective composition of Blotong, molasses, bran, and coconut husk for composting using MOL activator of stale rice and Trichoderma sp. according to SNI 7763:2018, and to determine the most effective composting time. The ratio of Blotong, coconut husk, bran, and molasses for the three variations were 56:10:30:4; 66:10:20:4; and 76:10:10:4 in percent as much as 6 kg calculated with Takakura method. The result of the study showed the three variations had fulfilled SNI 7763:2018 in 18 days, with the most effective composition is the 3rd variation.